Adab Sosial Al-Ghazali dalam Bidayatul Hidayah: Solusi Interaksi Sosial Remaja di Era Modern - Naufal Siregar, Adnan Faris; Siregar, Ali Nurdin (HUNAFA Jurnal Studia Islamika, 2024)
This study examines the relevance of Al-Ghazali's concept of social interaction in the book Bidayatul Hidayah as a solution to the challenges of adolescent social interaction in the digital era. Using a qualitative research method with a literature study approach, this study analyzes Al-Ghazali's teachings on social etiquette and ethics and their contextualization with the reality of modern adolescent social interaction. The results of the study indicate that Al-Ghazali's principles, such as being careful in interacting and avoiding useless conversations, have significant relevance in dealing with contemporary issues such as cyberbullying and social media addiction. Practical implementations of this concept include developing digital self-awareness, online communication ethics, and emotional management in digital interactions. In conclusion, the integration of Al-Ghazali's teachings into adolescent character education has the potential to create a more ethical and constructive model of social interaction in the digital era, while maintaining essential human values.